2004
DOI: 10.2527/2004.8271957x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exogenous ghrelin on feed intake, weight gain, behavior, and endocrine responses in weanling pigs1

Abstract: The objectives were to determine relative ADG, ADFI, behavior, and endocrine responses in weaned pigs receiving exogenous ghrelin. Twenty-four barrows weaned at 18 d of age (d 0 of the experiment) were catheterized via the jugular vein, weighed, and assigned to either a ghrelin (n = 12) or saline (control; n = 12) infusion group. Initial pig BW did not differ between treatments (7.87+/-0.39 vs. 7.92+/-0.35 kg for ghrelin and control treatments, respectively). Pig BW and feed intakes were measured once daily th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
48
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 47 publications
6
48
3
Order By: Relevance
“…The ghrelin protein level was about 50 pg/ml and it was accordance with literature data (Salfen et al, 2004). Our results showed that polymorphism located in promoter region (c.-93A>G) affected expression level of GHRL gene.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The ghrelin protein level was about 50 pg/ml and it was accordance with literature data (Salfen et al, 2004). Our results showed that polymorphism located in promoter region (c.-93A>G) affected expression level of GHRL gene.…”
Section: Discussionsupporting
confidence: 91%
“…However, the most important factor which regulates the expression and release of ghrelin is feed intake (fasted or fed). Starvation increases ghrelin expression in the gastric fundus and ghrelin peptide content in blood (Salfen et al, 2004). Some reports showed that in pig, nutrient content of the diet regulates ghrelin expression at the post-transcriptional level Yin et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Weaning is considered one of the most stressful periods that has a negative impact on feed intake and BW control, hence influencing ghrelin secretion (Salfen et al, 2004). Our results did not show an effect at 28 days of age (age of weaning) on the amount of gastric GCs nor total ghrelin serum concentrations.…”
Section: Discussioncontrasting
confidence: 73%
“…However, research of Du et al (2007) indicates that changes only appear 10 days after weaning. Interestingly, exogenous ghrelin induces weight gain in weaning piglets (Salfen et al, 2004). Therefore, further research is needed on GC development and ghrelin secretion in piglets within the weaning period.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of Trp on feed intake may also be caused by its effect on gastric emptying (Sè ve, 1999) or on ghrelin (Zhang et al, 2007). Ghrelin is a peptide hormone secreted by the stomach and the duodenum, and is involved in the regulation of feed intake and in the signalling between the digestive system and the brain (Inui et al, 2004;Salfen et al, 2004).…”
Section: Data Selection and Relevance Of The Recalculation Of The Nutmentioning
confidence: 99%